Spectral Correlation Technique for Determination of Property Constants of Cadmium Complex with o-Nitrobenzenediazoaminoazobenzene and Determination of Trace Amounts of Cadmium - Yanga, Jia-Xiang; Kong, Xian-Tai; Shi, Shu-Ren; Gao , Hong-Wen; Wang, Lei; Liu, Qing-Liang (Asian Journal of Chemistry, 2010)
The ligand, o-nitrobenzenediazoaminoazobenzene (o-NBDA) was synthesised and its reaction with cadmium(II) was sensitive in basic solution in presence of the non-ionic surfactant emulsifier OP. Because of the serious influence of excess of the ligand, the spectral correction technique was used in place of ordinary spectrophotometry. This method gave the simple determination of property constants of the Cd-o-NBDA complex and the results showed the complex was Cd(o-NBDA)4, its real molar absorptivity ε480nm = 1.02 x 105 L mol-1 cm-1 and its cumulative stability constant K = 2.15 X 1023. For analysis of samples, the recovery was between 91.0 and 08.5% and the relative standard deviation (RSD) is less than 6%.